Pengaruh Konvergensi IFRS, Struktur Kepemilikan Saham, Tata Kelola Perusahaan, dan Kualitas Audit Terhadap Manajemen Laba - Agustina Santoso (Jurnal Akuntansi Bisnis, 2016)
Abstract The purpose of this research is to analyze the effect of the convergence of IFRS, ownership structures measured with managerial ownership and institusional ownership, good corporate governance mechanisms measured with independence of the board of director and comitte audit, and audit quality on the earning management. Earning management is measured with Ball and Shivakumar model (2005). The samples of this research are 103 nonfinancial companies listed on Indonesian Stock Exchange in 2009-2013. The result showed that convergence of IFRS, managerial ownership, institusional ownership, independence of the board of director, and comitte audit have a negative significant effect on earning management. Audit quality have a negatife significant effect on earning management.